Unraveling the Dynamic Nexus Between Trade Liberalization, Energy Consumption, CO2 Emissions, and Health Expenditure in Southeast Asian Countries - Akbar A; Rehman A; Ullah I; Zeeshan M; Afridi FEA (Dove Medical Press, 2020)
Ahsan Akbar,1 Alam Rehman,2 Irfan Ullah,3 Muhammad Zeeshan,4 Fakhr E Alam Afridi5 1International Business School, Guangzhou College of South China University of Technology, Guangzhou 510080, People’s Republic of China; 2Faculty of Management Sciences, National University of Modern Languages, Islamabad, Pakistan; 3Reading Academy, Nanjing University of Information Science and Technology, Nanjing, People’s Republic of China; 4College of Business Administration, Liaoning Technical University, XingCheng, Liaoning Province 125105, People’s Republic of China; 5Islamia College Peshawar, Peshawer, PakistanCorrespondence: Alam RehmanFaculty of Management Sciences, National University of Modern Languages, Islamabad, PakistanEmail amrehman@numl.edu.pkObjective: Most of the Southeast Asian countries witnessed remarkable economic growth in the last few decades. Trade is a primary factor in achieving this exponential economic progress in these countries. Besides, the positive implications of trade, it has associated cost of escalated energy consumption, CO2 emissions, and resulting health complications which leads to higher public health expenditures. This study examines the nexus between trade liberalization, energy consumption, CO2 emissions, and health expenditures in Southeast Asian countries for the period of 1991 to 2018.Methods: The empirical methods used in this study entail diagnostic testing, correlation analysis, and structure equation modeling (SEM) technique. SEM is an advanced multivariate analysis technique that can test complex multivariate causal associations among a set of variables. Therefore, it is the most suitable econometric approach to explore the dynamic association between trade openness, energy consumption, CO2 emissions, and health expenditures.Results: The empirical results reveal a nexus between trade openness, energy consumption, CO2 emissions, and health expenditure in Southeast Asian countries. Nevertheless, pollutant emissions have a direct impact on health expenditures, whereas trade and energy consumption shows an indirect influence on the escalation in public health spending in sample Southeast Asian countries. Moreover, the mediating path of each indirect effect is energy consumption.Conclusion: These results imply that Southeast Asian countries heavily rely on fossil energy to fuel economic growth. Hence, to promote sustainable and eco-friendly economic development, the respective governments need to reform their energy sectors by tapping into renewable energy resources and deploy green technologies to reduce pollutant emissions for the development of a healthy society. In addition, governments should levy taxes on highly polluting industries so as to curtail carbon emissions and resulting health expenditures.Keywords: trade liberalization, energy consumption, CO2 emissions, health expenditures, Southeast Asia